Ten questions concerning soundscape valuation. (1st July 2022) - Jiang, Like; Bristow, Abigail; Kang, Jian; Aletta, Francesco; Thomas, Rhian; Notley, Hilary; Thomas, Adam; Nellthorp, John
Abstract: The past two decades have seen an ongoing paradigm shift from noise control to soundscaping, and soundscape approaches have been applied in noise management projects. However, cost-benefit analysis (CBA), which is widely used for economic appraisal of projects that would impact on the sound environment, remains noise-based and residential-location-focused. As a result, benefits of wanted sounds are omitted from appraisal. While there is a wealth of literature seeking to place a value/cost on changes in noise exposure, little research has been done on soundscape valuation. Consequently, there is little evidence on the monetary value of soundscape, which is essential for developing soundscape-based CBA. This paper initiates a systematic discussion on this emerging topic, by addressing ten questions covering the definition and scope for soundscape valuation, potential valuation methods for primary soundscape valuation research and required data, special concerns on private and public contexts, non-monetary valuation and soundscapes of cultural and/or historical significance, and the eventual application of soundscape values in CBA and beyond. Answers are based on reflection of existing literature on environmental valuation and soundscape, and visionary opinions by the authors from research, practice and policy sectors, and can help establish a framework to support future research in soundscape valuation and relevant areas. Highlights: The needs for soundscape valuation are explained and scope suggested. Potential valuation methods for soundscape valuation are compared. Data requirements, social and non-monetary values, and special soundscapes are also discussed. Applications of soundscape values for cost-benefit analysis and beyond are suggested.